2017
DOI: 10.4329/wjr.v9.i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of imaging in assessing harmful effects on spermatogenesis in adult testes with varicocele

Abstract: Varicocele is characterized by an abnormal dilatation and retrograde blood flow in the spermatic veins. Varicocele is the leading correctable cause of male infertility. Although it is highly prevalent in infertile men, it is also observed in individuals with normal fertility. Determining which men are negatively affected by varicocele would enable clinicians to better select those men who will benefit from treatment. To assess the functional status of the testes in men with varicocele, color Doppler sonographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 97 publications
0
24
0
2
Order By: Relevance
“…Testicular arterial blood flow is significantly reduced in men with varicocele, reflecting an impairment of spermatogenesis (Tsili et al, ). It is hypothesised that impaired venous drainage leads to increase in testicular veins pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular arterial blood flow is significantly reduced in men with varicocele, reflecting an impairment of spermatogenesis (Tsili et al, ). It is hypothesised that impaired venous drainage leads to increase in testicular veins pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Varicocele is the most common andrological disorder among adolescents and adult males with an incidence of 15%–20%. It is associated with 35% and 69% of primary and secondary infertility cases respectively (Baigorri & Dixon, ; Gat et al, ; Tsili et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MRI/MRS may also be valuable clinical tools. For example, MRI can be used in humans to visualise intratesticular lesions (22-24), testicular tumours (25), torsion (21, 26), varicoceles (27, 28) and testicle location (29) at common clinical MR field strengths. Reduction in testicular size, epididymis diameter or seminiferous tubule diameter (30) may be markers of disrupted spermatogenesis, and the size of either could thus potentially be used as an indicator of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the controlled environmental conditions, harmful factors such as varicocele, testicular torsion and environmental impacts of oxygen deficiency (hypoxia) can cause changes in the blood flow, nutrition and oxygenation of male germ cells as well negative effects on the function of these cells and thus lead to reduced fertility or infertility (Liao et al., ; Tsili et al., ; Verratti et al., ). Previous studies have expressed that DNA damages and apoptosis of germ cells are common features found in hypoxia, varicocele and testicular torsion (Liao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, hypoxia can reduce fertility in humans and rats. Clinical and experimental studies have indicated that hypoxia can reduce the number and motility of sperm, cause degenerative changes and increase the apoptosis of germ cells in seminiferous tubules (Liao et al., , ; Reyes et al., ; Tsili et al., ). In addition, the previous study showed that hypoxia causes functional and histopathological changes in the testis of neonatal rats (Liu & Du, ).…”
Section: Introductionmentioning
confidence: 99%